2013
DOI: 10.1186/1471-2229-13-49
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis indicates massive changes in metabolism prior to the inhibition of growth and photosynthesis of grapevine (Vitis vinifera L.) in response to water deficit

Abstract: BackgroundCabernet Sauvignon grapevines were exposed to a progressive, increasing water defict over 16 days. Shoot elongation and photosynthesis were measured for physiological responses to water deficit. The effect of water deficit over time on the abundance of individual proteins in growing shoot tips (including four immature leaves) was analyzed using nanoflow liquid chromatography - tandem mass spectrometry (nanoLC-MS/MS).ResultsWater deficit progressively decreased shoot elongation, stomatal conductance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 87 publications
5
86
1
Order By: Relevance
“…Furthermore, Sánchez-Rodríguez et al (2011) indicate that drought stress resulted in decreased shikimate pathway and phenolic compounds in the tomatoes more sensitive to water stress. In grapevine, water deficit decreased shoot elongation, stomatal conductance and photosynthesis, and the protein level of 3-phosphoshikimate 1- carboxyvinyltransferase was also progressively reduced by water deficit treatment (Cramer et al 2013). To above results, protein synthesis pathways were up-regulated in L6138, but down-regulated in L0994.…”
Section: Comparison Of Overall Changes In Protein Levels Among Stressmentioning
confidence: 68%
“…Furthermore, Sánchez-Rodríguez et al (2011) indicate that drought stress resulted in decreased shikimate pathway and phenolic compounds in the tomatoes more sensitive to water stress. In grapevine, water deficit decreased shoot elongation, stomatal conductance and photosynthesis, and the protein level of 3-phosphoshikimate 1- carboxyvinyltransferase was also progressively reduced by water deficit treatment (Cramer et al 2013). To above results, protein synthesis pathways were up-regulated in L6138, but down-regulated in L0994.…”
Section: Comparison Of Overall Changes In Protein Levels Among Stressmentioning
confidence: 68%
“…Recently, Cramer et al (31) reported that numerous proteins involved in glycolysis were significantly affected by water deficit in grapevine, indicating that these changes in plant metabolism appeared to antioxidant defenses in the very early stages of plant response to water deficit before significant injury. Specifically, the levels of hexokinase-1, glyceraldehyde-3-phosphate dehydrogenase, triose phosphate isomerase, phosphoglycerate kinase, malate dehydrogenase, and malic enzyme were increased, whereas those of phosphoglycerate mutase, phosphoglucomutase, phosphofructokinase, and pyruvate kinase were decreased on 4 day of the water deficit treatment (31). In the present study, pyruvate kinase was increased under flooding stress, but was not identified as a differentially abundant protein under drought stress.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…511 Currently, stable isotopic labeling followed by reverse phase high-performance liquid chromatography coupled with tandem mass spectrometry (HPLC–MS/MS) is successfully used to characterize and quantify changes in protein levels in V. vinifera . 9,10,12 …”
Section: Introductionmentioning
confidence: 99%